2021
DOI: 10.1108/sjme-04-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional experience and destination image on ecotourism satisfaction

Abstract: Purpose The purpose of this study is to analyze the influence of the emotional experience (EE) and the image of the tourist destination on the satisfaction of the domestic tourist and his behavioral intentions, represented through the word of mouth (WOM) and his revisit intention. Design/methodology/approach The information obtained through a personal survey to 382 local tourists was refined and subjected to structural equation analysis. Analyses conducted with SPSS 20.0 and AMOS 20 software confirmed the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 82 publications
3
20
1
1
Order By: Relevance
“…Additionally, the tourism experience had an indirect effect on loyalty (including destination loyalty and ecotourism loyalty) through the mediating effects of destination image and satisfaction. Along the same lines, scholars Quynh et al [74] analyzed Vietnamese tourists who had visited ecological destinations, and identified that the positive image of the destination and the different experiences are considered the main elements that promote positive emotions and satisfaction in tourists, leading to greater eagerness for spreading WOM recommendations and revisiting a destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the tourism experience had an indirect effect on loyalty (including destination loyalty and ecotourism loyalty) through the mediating effects of destination image and satisfaction. Along the same lines, scholars Quynh et al [74] analyzed Vietnamese tourists who had visited ecological destinations, and identified that the positive image of the destination and the different experiences are considered the main elements that promote positive emotions and satisfaction in tourists, leading to greater eagerness for spreading WOM recommendations and revisiting a destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social scientists continuously explore the characteristics that can influence tourist loyalty, considering the practical implication of destination loyalty. Tourist loyalty studies can be summarized as motivation factors (Suhartanto et al, 2020a ), demographic characteristics (Stojanovic et al, 2017 ), past experiences (Chang et al, 2014 ), destination image (Lee and Xue, 2020 ), service quality (Alexandris et al, 2006 ), perceived quality (Shahijan et al, 2018 ), satisfaction (Quynh et al, 2021 ), and novelty (Chang et al, 2014 ). Based on these antecedents, the researchers have developed numerous theoretical frameworks to understand the formation process of tourist loyalty (Cossío-Silva et al, 2019 ; Lee and Xue, 2020 ; Quoquab et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of ecotourism, experience is defined as the “culmination of a given experience formed by tourist while they are traveling and spending time at a given destination” (Chan and Baum, 2009 ). Quynh et al ( 2021 ) studied the role of experience in the context of emotions and their ability to influence the destination image, consequently affecting the destination satisfaction level. Chan and Baum ( 2009 ) consider the ecotourism experience as hedonic, interactive, novel, comforting, safe, stimulating, and vital in establishing the tourist attachment to the destination.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations